Knowledge translation and implementation of housing first in Canada: A qualitative assessment of capacity building needs for an evidence-based program. (August 2019) - Hasford, Julian; Nelson, Geoffrey; Worton, S. Kathleen; Macnaughton, Eric; MacLeod, Tim; Piat, Myra; Tsemberis, Sam; Stergiopoulos, Vicky; Distasio, Jino; Aubry, Tim; Goering, Paula
Highlights: Capacity building needs for communities implementing Housing First (HF) include clarification of HF principles, clinical skills, landlord engagement, client prioritization, and fidelity assessment. An Interactive approach to Knowledge Translation approach can facilitate the real-time utilization of evaluation findings. Qualitative approaches to training and technical assistance (TTA) needs assessments can ensure that TTA activities are tailored to local implementation stage and contexts. Abstract: We examined communities' expressed needs for capacity building in the implementation of Housing First (HF) for persons experiencing homelessness. The findings are based on thematic analyses of qualitative data obtained from participants ( n = 77) in 11 focus groups conducted in seven Canadian cities. We identified capacity building needs in the areas of training (e.g., HF principles, clinical services, landlord engagement) and technical assistance (e.g., intake coordination, client prioritization, fidelity assessment). These findings were used to tailor training and technical assessment (TTA) to the stages of HF implementation in these cities. Limitations and implications for future theory, research, and practice are discussed.